On the Genesis of the ‘Sustainable Security’ Concept - E. N. Glazunova (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
Contemporary specialist in development studies use a variety of similar terms often incoherently. In particular, this observation applies to the concept of ‘security’. While the term ‘sustainable development’ is now firmly established in theory and policy, the ‘security’ concept remains essentially contested. In the relevant literature ‘sustainable development’ may be linked to ‘environmental security’, ‘human security’ or ‘sustainable security’. Acknowledging the existence of an inextricable ‘security — development nexus’, the author traces the modifications of its first element. Examination of the concepts used in an academic discourse over the last three decades — since the emergence of ‘sustainable development’ paradigm allows to reconstruct the genesis of ‘sustainable security’, one of the most recent entries to international development lexicon. This paper demonstrates that initially, when ‘sustainable development’ concept had just emerged, the nexus was seen as a dyad ‘sustainable development — environmental safety’. At the very end of the 20th century, scholars came up with a new modification of the nexus — ‘human security — sustainable development’. However, the process of its conceptualization was disrupted by the so-called ‘securitization of development’. The international development community’s responded to this disruption with a ‘sustainable security’ concept. Describing the key parameters of ‘sustainable security’, the author emphasizes that a unified and holistic approach to its conceptualization is yet to be formed in the Western development community.